Afloramento - modelo da Formacao Piramboia - Caetano-Chang, M. R.; Fu Tai Wu, (My University, 1994)
This short paper describes an outcrop that is a very good example of the aeolian sedimentation in the Piramboia Formation (Triassic) in the Parana Basin. -English summary
Model outcrop of the Piramboia Formation
Keywords: aeolian deposit; palaeoenvironment; sedimentation; stratigraphy; Triassic; Brazil, Parana Basin